PENGEMBANGAN MODEL PEMBELAJARAN FLIPPED CLASSROOM DENGAN TAKSONOMI BLOOM PADA MATA KULIAH SISTEM POLITIK INDONESIA - Zamzami Zainuddin (Universitas Muhammadiyah Ponorogo, 2019)
This study aims to provide the design of the flipped learning instructional model for teaching Indonesian Political System course at an Indonesian higher education institution. A bottom-up of flipped learning model based on Blooms’ taxonomy of cognitive domain was developed. Social media WhatsApp group was employed as a platform to share the recorded YouTube video lectures for students’ learning activities outside-of-class. Before students attend class, they have prepared with the lesson’s content, hence in-class activities are utilized for homework, hands-on activities, and group discussions. In other words, watching, summarizing, and note-taking are the main activities proposed by a researcher outside of the classroom, whereas Socratic questioning through a group discussion is the main activities in the classroom. This study suggests that the bottom-up of flipped learning model is potentially implemented for teaching any social studies course at any higher education institution, with the aim of promoting students’ highest level of cognitive domains or higher-order thinking skills. This study has implications for Ministry of Research, Technology and Higher Education (Ristekdikti) or policymaker to determine the flip-class pedagogy as a contemporary teaching model for teaching any course in Indonesian higher education.